Online customer shopping behaviour: The mediating role of online perceived risk - Yahya, Wan Kalthom; Hashim, Nor Hashima; Husin, Norhusniyati; Abdul Rahim, Najihah (Othman Yeop Abdullah Graduate School of Business, 2020)
The studies of online purchase intention have been done extensively throughout the world by testing many predictors. Due to the rapid growth of technological advances affecting internet users suggest other new predictors considered as an online purchase intention element. This study suggests customer review, online store image, and perceived online risk (an element of a mediating factor) as three main variables that drive customers to purchase online. A simple convenience sampling method was used to analyse the responses from online users via the online questionnaire web surveys. Multiple regressions and Sobel tests were used in this study to test the hypotheses. The result shows that online customer review and online store image have a positive relationship with the perceived risk online as well as perceived risk itself also has a positive relationship with online purchase intention. Consequently, in terms of mediating factors, perceived risk online is seen as a mediator for both online customer review and online store image with online purchase intention. Having said that, the study hopes that the findings would help boost the online retail industry as a contributor to the country's economic development.